Formulation and antioxidant properties of curcumin gum Arabic nanoparticles for delivery to cancer cells - Doolaanea, Abd Almonem; Hassani, A; Hussain, SA; Enezei, HH; Saeed, S; Ibrahim, WN; Al-Qubaisi, MS; Zentou, H; Rosli, R (IOP Publishing Ltd, 2020)
Curcumin nanoparticles)Cur/GANPs(were formulated based on gum arabic)GA(as a stabilizer coatings for nanoparticles through efficient synthesis approach . The current study investigated the antioxidant properties and antihypertensive activity of curcumin)Cur(using various established in vitro assays, such as 1,1-diphenyl-2-picrylhydrazyl)DPPH(as well as angiotensin converting enzyme (ACE(inhibitory activity. The in vitro cytotoxicity of Cur/GANPs against human liver cancer)HepG2(, and colon cancer)HT29(was investigated. The exposure of human cancer cells to Cur/GANPs)1.56-100 µg/ml(using MTT)3-)4,5-dimethylthiazol-2-yl(2,5-diphenyl tetrazolium bromide(has revealed that the Cur/GANPs inhibited the growth of cell lines examined in a dose dependent manner. Hence, Cur/GANPs nanoparticles may have great potential to be applied for cancer treatment.